If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 4y = 2z Solving 3x + 4y = 2z Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4y' to each side of the equation. 3x + 4y + -4y = -4y + 2z Combine like terms: 4y + -4y = 0 3x + 0 = -4y + 2z 3x = -4y + 2z Divide each side by '3'. x = -1.333333333y + 0.6666666667z Simplifying x = -1.333333333y + 0.6666666667z
| -15=-11+v | | x+500=17.548 | | 20=8+150k | | 4m+9-7m=-3(m-3) | | 5/2*-2 | | -7x+x^9= | | 2(3x-5)=6(x-2) | | 2x+3-5+7=10x+3-6x-4 | | 0.9x-0.2(15-5x)=0.4(x-4) | | 0.36x=26 | | 9/x+1-5/2=8/3x+3 | | .5x-6=.33 | | 10q^2+9q+2= | | .5-6=.33 | | (z-24)/8+2 | | 3x-2(x-1)=4x+20-2x | | 6(x-6)+12=3(x-7) | | 20=k-10 | | 5y^2+12y-32= | | w-3/4=7/4 | | 3x+9xy-30x=0 | | 1/2k+5=k+3 | | 3(a+2)=2(a+3)-3 | | 14x+5y=296 | | (6*-2)+6(2)/6-2 | | 6+5p-2=8p+4-2p | | 8+4x+7=3x+3-5x | | (4m^6+3m^5-6m^7)/m^2 | | c^2a^3b-cab^3=0 | | p-4=-9-p | | 10-9=9+6x-9 | | (4x-2)-(7x+2)= |